Peranan Pendidikan Seni Budaya Terhadap Kehidupan Sosial Budaya - Asidigisianti S.p, ; Marsudi, (Pendidikan Sekolah Dasar, 2009)
Arts education has a multilingual nature, multidimensional, and multicultural, and also plays a role in the formation of personal or mental attitude of harmonious learners, for cultural arts education focusing on child development needs in achieving emotional intelligence and social intelligence. Emotional intelligence is achieved by themselves through physical exercises to improve the sensitivity and refinement and beauty will appreciation arts and culture, and competence to express it. Social intelligence is achieved through: fostering and nurturing reciprocal relationships; democratic, empathetic and sympathetic; uphold human rights; cheerful and confident; appreciate diversity in society and the state; and insightful with a teacher of nationality rights and obligations of citizens.